Measuring an understudied factor in medical education: development and validation of the medical curiosity scale - Bugaj, Till Johannes; Schwarz, Tim Alexander; Terhoeven, Valentin; Nagy, Ede; Cranz, Anna; Friederich, Hans-Christoph; Nikendei, Christoph (Medical education online, 2023)
Curiosity, which has been called the third pillar of academic achievement and positively predicts academic performance (von Stumm et al., 2011), is widely recognized as an important factor in acquiring knowledge and skills in medical training, and may be critical for students´ sound mental health. Medical educators have advocated that curiosity should play a more significant role in medical training and have criticized didactic barriers impeding student curiosity. However, in medical training, curiosity is understudied partly due to a lack of methods for measuring curiosity. Therefore, this study was designed to develop and validate a scale to measure medical curiosity. After reviewing the literature and interviewing a panel of experts (n = 7), 25 preliminary items assessing medical curiosity were developed and administered to n = 305 medical students (n = 163 female and n = 142 male) at Heidelberg University across all medical school years. Following exploratory factor analysis (EFA) with oblique (promax) rotation, we measured medical curiosity in a medical student sample. We have identified two distinct factors: intellectual medical curiosity (IMC) and social medical curiosity (SMC). IMC describes the desire to acquire medical knowledge for curiosity’s sake, while SMC refers to curiosity about human nature and, in particular, patient health. Both factors showed good psychometric properties, with eigenvalues of 6.7 and 3.5, explaining 26.6% and 14.0% of the variance and internal consistencies of 0.796 and 0.866, respectively, and high convergent and discriminant validity. While first-year students showed significantly higher IMC scores than final-year medical students, SMC scores remained stable and tended to increase throughout medical school. This study has succeeded in developing the first scale to measure aspects of medical curiosity and, thus, lays the groundwork for future studies examining medical students’ curiosity. A deeper understanding of medical students’ curiosity can help to foster this curiosity effectively.
Gesehen am 24.05.2023